Isolation and characterization of biosurfactant/bioemulsifier-producing bacteria from petroleum contaminated sites - Batista, S.B.; Mounteer, A.H.; Amorim, F.R.; Totola, M.R.
Biosurfactant-producing bacteria were isolated from terrestrial and marine samples collected in areas contaminated with crude oil or its byproducts. Isolates were screened for biosurfactant/bioemulsifier production in different carbon sources (glucose, fructose, sucrose and kerosene)using the qualitative drop-collapse test. Glucose produced the highest number of positive results (17 of 185 isolates). All 17 isolates produced emulsions with kerosene and 12 exhibited high emulsion-stabilizing capacity, maintaining 50
Keywords: BIOSURFACTANTS; BIOEMULSIFIERS; CRITICAL MICELLE CONCENTRATION; EMULSION STABILITY; PETROLEUM CONTAMINATION